Penyelesaian Sengketa Dalam Perjanjian Lisensi Merek - Muhammad Setya Ady Syarifuddin (Simbur Cahaya, 2019)
Consensus agreement is a way of resolving disputes, but if the consensus agreement is not reached, the problem of resolving disputes over service brand licensing agreements which are generally civil matters can be filed in the District Court as agreed. This type of research is normative juridical research. Results obtained, the licensing agreement is different from the transfer of rights because it is only a license to use the brand, not to transfer the rights of the brand so that the rights to the brand still exist with the licensor as the brand owner or the holder of their rights. Making and implementing license agreements is based on the principle of agreement in general contract law. This, not only provides a legal guarantee for the licensee to use the licensee brand, for the brand owner is a protection as well as the controller that his brand is used by the licensee with permission and knowledge from him.